2018
DOI: 10.1007/s40618-018-0919-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of EIF1AX in thyroid cancer tumourigenesis and progression

Abstract: According to our results, distinct mutations on EIF1AX may be related to different phenotypes/behaviours. Despite being a small series, which reflects the difficulty in retrieving PDTC and ATC surgical samples with well-differentiated and/or benign areas, our study may provide new insights into thyroid cancer tumourigenesis and dedifferentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…Co-occurrence of EIF1AX and H/N/K-RAS mutations is correlated with tumor aggressiveness, especially when it is the A113_splice mutations for EIF1AX gene [15, 25]. That is consistent with our results that EIF1AX mutations in FTC were located at intron 5/exon 6, correlated with advanced disease, and coexisted with NRAS mutation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Co-occurrence of EIF1AX and H/N/K-RAS mutations is correlated with tumor aggressiveness, especially when it is the A113_splice mutations for EIF1AX gene [15, 25]. That is consistent with our results that EIF1AX mutations in FTC were located at intron 5/exon 6, correlated with advanced disease, and coexisted with NRAS mutation.…”
Section: Discussionsupporting
confidence: 90%
“…2. In order to have an overall understanding of EIF1AX mutation detected in thyroid tumors, we also analyzed the occurrence of EIF1AX mutations in the COSMIC database [23], cBioPortal for cancer genomics database [24] and previous studies [14, 15, 2529] (Table 2). EIF1AX intron5/exon6 mutations occurred in benign or malignant thyroid tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies, the most common type of EIF1AX mutation identified in our study was the A113_splice mutation at the intron 5/exon 6 splice site of EIF1AX (17/26), followed by the missense mutations in N-terminus of the protein (5/26). Previous studies have concluded that the A113_splice mutation, especially with co-existing RAS mutation, is more frequently observed in thyroid cancer than isolated EIF1AX mutations or mutations at the N-terminus hotspot of the gene (4,11,14). In our study, 13/17 (76.5%) surgically resected nodules with the A113_splice mutation and 3/5 (60%) nodules with an N-terminal missense mutation were malignant.…”
Section: Discussionsupporting
confidence: 43%
“…Originally identified in uveal melanomas, EIF1AX mutations have now also been detected in a variety of other tumor types, including low-grade gliomas, lung adenocarcinoma, endometrial carcinoma, and various neoplastic and nonneoplastic thyroid lesions (4,(9)(10)(11). Missense mutations of the first 2-15 amino acids at the N-terminus of EIFIAX have been identified in several cancers (9,(12)(13)(14). An additional hotspot splice-site mutation (A113_ splice) in the C-terminus of the protein is thought to be exclusive to thyroid carcinoma (9,11,15).…”
Section: Discussionmentioning
confidence: 99%